Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Using the limit definition of the derivative which I know is: $$f'(x)=\lim_{h\to0}\left(\frac{f(x+h)-f(x)}{h}\right)$$ I am trying to solve this problem $$f(x)= \frac{x}{x+2} $$

How do I go about properly solving this, I seemed to get

$$\frac{x}{x+2}\ $$ as my answer again? What are the steps I should follow?

I am trying to find the derivative of $f(x)= \frac{x}{x+2}$ using the definition of the derivative.

share|cite|improve this question
What do you mean? Can please state clearly what the problem is? – Mercy King Jun 22 '12 at 17:37
I am trying to find the derivate of f(x)= x/x+2 using the function of the derivative. – soniccool Jun 22 '12 at 17:38
@mystycs: Using the definition of the derivative? (Rather than the "function" of the derivative, which, frankly, doesn't parse?) – Arturo Magidin Jun 22 '12 at 17:50
up vote 3 down vote accepted

I'm supposing you want to find the derivative using the limit definition.

$\begin{align*}f'(x) &= \lim_{h\to 0}\frac{f(x+h)-f(x)}{h} = \lim_{h \to 0 } \frac{\frac{x+h}{x+h+2} - \frac{x}{x+2}}{h} = \lim_{h \to 0 }\frac{x^2+2x+hx+2h-x^2-xh-2x}{h(x+h+2)(x+2)} = \\ &= \lim_{h \to 0 }\frac{2h}{h(x+h+2)(x+2)} = \lim_{h \to 0 }\frac{2}{(x+2)(x+h+2)} = \frac{2}{(x+2)^2} \end{align*}$

You should probably check your algebra. Subtracting the fractions may be a bit tricky.

share|cite|improve this answer
I think its the algebra yea im looking over it now – soniccool Jun 22 '12 at 18:11

$f(x) = \frac{x+2 - 2}{x+2} = 1 - \frac{2}{x+2}$

$$\frac{f(x+h) - f(x)}{h} = \frac{\frac{2}{x+2} - \frac{2}{x+h+2}}{h} = \frac{2}{h} \cdot \frac{x+h+2 - (x+2)}{(x+2)(x+h+2)} = \frac{2}{(x+2)(x+h+2)} \xrightarrow{h\to 0} \frac{2}{(x+2)^2}$$

share|cite|improve this answer

First note that your definition of derivative is incorrect. The derivative of a function $f(x)$ at a point $x$ is defined as $$f'(x) = \color{red}{\lim_{h \to 0}} \dfrac{f(x+h) -f(x)}h$$ Note that you need to take the $\color{red}{\displaystyle \lim_{h \to 0}}$ to get the derivative at $x$. Taking the limit as $h \to 0$ is the most important step.

Now lets get back to your problem. The function you have is $f(x) = \dfrac{x}{x+2}$. Hence, \begin{align} f'(x) & = \lim_{h \to 0} \dfrac{f(x+h) -f(x)}h = \lim_{h \to 0} \dfrac{\dfrac{x+h}{x+h+2} -\dfrac{x}{x+2}}h\\ & = \lim_{h \to 0} \dfrac{\dfrac{(x+h)(x+2) - x(x+h+2)}{(x+h+2)(x+2)}}h\\ & = \lim_{h \to 0} \dfrac{\dfrac{x^2 +2x+hx+2h - x^2-xh -2x}{(x+h+2)(x+2)}}h\\ & = \lim_{h \to 0} \dfrac{\dfrac{2h}{(x+h+2)(x+2)}}h\\ & = \lim_{h \to 0} \dfrac2{(x+h+2)(x+2)}\\ & = \dfrac2{\lim_{h \to 0} (x+h+2)(x+2)}\\ & = \dfrac2{(x+2)^2} \end{align} Hence, the derivative of $\dfrac{x}{x+2}$ is $\dfrac2{(x+2)^2}$.

share|cite|improve this answer

First. The derivative function of $f(x)$ is not $\frac{f(x+h)-f(x)}{h}$. (That would be a function of two variables, $x$ and $h$). Rather, the derivative function of $f(x)$ is $$\lim_{h\to 0}\frac{f(x+h)-f(x)}{h}.$$ The limit is important. Without the limit, it's just plain wrong.

Second. I don't know how you "got back" $f(x)$. The computations aren't that bad, just lots of algebra; perhaps you substituted incorrectly?

$$\begin{align*} f(x) &= \frac{x}{x+2}\\ f(x+h) &= \frac{(x+h)}{(x+h)+2} = \frac{x+h}{x+h+2}\\ f(x+h) - f(x) &= \frac{x+h}{x+h+2} - \frac{x}{x+2}\\ &= \frac{(x+h)(x+2)}{(x+h+2)(x+2)} - \frac{x(x+h+2)}{(x+2)(x+h+2)}\qquad\text{(common denominator)}\\ &= \frac{(x+h)(x+2) - x(x+h+2)}{(x+2)(x+h+2)}\\ &= \frac{x(x+2) + h(x+2) - x(x+2) - xh}{(x+2)(x+h+2)}\\ &= \frac{h(x+2-x)}{(x+2)(x+h+2)}\\ &= \frac{2h}{(x+2)(x+h+2)}. \end{align*}$$ Therefore, $$\begin{align*} f'(x) &= \lim_{h\to 0}\frac{f(x+h)-f(x)}{h}\\ &= \lim_{h\to 0}\frac{\quad\frac{2h}{(x+2)(x+h+2)}\quad}{h}\\ &= \lim_{h\to 0}\frac{2h}{h(x+2)(x+h+2)}\\ &= \lim_{h\to 0}\frac{2}{(x+2)(x+h+2)} \qquad\text{(since }h\neq 0\text{, so we can cancel)}\\ &= \frac{2}{(x+2)(x+0+2)} \qquad\text{(since the function is defined at }h=0\text{)}\\ &= \frac{2}{(x+2)^2}. \end{align*}$$

share|cite|improve this answer

I think that you mean that you want to use the definition of the derivative to find the derivative of the function $$f(x)=\frac{x}{x+2}\;.$$ The definition is that $$f\,'(x)=\lim_{h\to 0}\frac{f(x+h)-f(x)}h\;.$$ Note the limit: it’s essential.

For your function this is

$$\begin{align*} \lim_{h\to 0}\frac{\frac{x+h}{(x+h)+2}-\frac{x}{x+2}}h&=\lim_{x\to 0}\left(\frac1h\left(\frac{x+h}{(x+h)+2}-\frac{x}{x+2}\right)\right)\\ &=\lim_{h\to 0}\left(\frac1h\cdot\frac{(x+2)(x+h)-x(x+2+h)}{(x+2)(x+2+h)}\right)\\ &=\lim_{h\to 0}\frac{x^2+2x+hx+2h-x^2-2x-hx}{h(x+2)(x+2+h)}\\ &=\lim_{h\to 0}\frac{2h}{h(x+2)(x+2+h)}\\ &=\lim_{h\to 0}\frac2{(x+2)(x+2+h)}\;, \end{align*}$$

where I’ve simply put the original numerator $f(x+h)-f(x)$ over a common denominator and simplified. At this point we’ve managed to get rid of the factor of $h$ in the denominator, so we can take the limit: as $h\to 0$, the numerator just sits there at $2$, and the denominator approaches $(x+2)(x+2)$, or $(x+2)^2$. Thus,

$$f\,'(x)=\lim_{x\to 0}\frac2{(x+2)(x+2+h)}=\frac2{(x+2)^2}\;.$$

Added: By the way, if your algebra is good enough, you can notice that $$\frac{x}{x+2}=\frac{(x+2)-2}{x+2}=1-\frac2{x+2}\;.$$ Then

$$\begin{align*} f(x+h)-f(x)&=\left(1-\frac2{(x+h)+2}\right)-\left(1-\frac2{x+2}\right)\\ &=\frac2{x+2}-\frac2{x+2+h}\\ &=\frac{2\big(x+2+h-(x+2)\big)}{(x+2)(x+2+h)}\\ &=\frac{2h}{(x+2)(x+2+h)}\;, \end{align*}$$

and you reach the point of being able to take the limit a bit more easily.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.